2021
DOI: 10.1002/jmri.27769
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Bone Marrow Fat Fraction and Iron by MRI for Distinguishing Aplastic Anemia from Myelodysplastic Syndromes

Abstract: Background: Bone marrow of patients with aplastic anemia (AA) is different from that of patients with myelodysplastic syndrome (MDS) and is difficult to identify by blood examination. IDEAL-IQ (iterative decomposition of water and fat with echo asymmetry and least-squares estimation) imaging might be able to quantify fat fraction (FF) and iron content in bone tissues. Purpose: To determine if IDEAL-IQ measurements of bone marrow FF and iron content can distinguish between patients with AA and MDS. Study Type: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
1
10
0
2
Order By: Relevance
“…Compared with other sequences such as T1-in-and-out-of-phase (IOP) MRI, CSE-MRI is a more sophisticated fat quantification approach which corrects for a number of confounding factors including T1 bias, noise bias and eddy currents ( 17 19 ). An iterative least-squares decomposition algorithm is used to solve for proton density fat fraction (PDFF) maps enabling the quantitative assessment of fatty lesions, which have been widely applied in the imaging of non-alcoholic fatty liver disease ( 20 , 21 ) as well as bone marrow fat in hematological diseases ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other sequences such as T1-in-and-out-of-phase (IOP) MRI, CSE-MRI is a more sophisticated fat quantification approach which corrects for a number of confounding factors including T1 bias, noise bias and eddy currents ( 17 19 ). An iterative least-squares decomposition algorithm is used to solve for proton density fat fraction (PDFF) maps enabling the quantitative assessment of fatty lesions, which have been widely applied in the imaging of non-alcoholic fatty liver disease ( 20 , 21 ) as well as bone marrow fat in hematological diseases ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, various physiological and pathological changes of bone marrow are closely related to fat content. Therefore, the quantification of fat content in bone marrow is of great clinical significance for evaluating the impact of various physiological and pathological processes on spinal bone marrow and screening of disease-related information ( 13 ). When compared with yellow bone marrow, red bone marrow contains a lower fraction of fat and a higher fraction of water ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…This index was examined for osteoporosis diagnosis and the differentiation of aplastic anemia and myelodysplastic syndrome. 37 Nevertheless, the diagnostic value of R2* in bone marrow lesions remains controversial. Liu et al investigated the quantitative MRI assessment of 83 patients with low back pain-results showed that R2* had a lower AUC than FF in diagnosing the progression of osteoporosis and osteopenia, making it difficult to use it as an independent diagnostic indicator for osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, R2* (equivalent to 1/T2*) was correlated with the microarchitectural structure of the bone marrow. This index was examined for osteoporosis diagnosis and the differentiation of aplastic anemia and myelodysplastic syndrome 37 . Nevertheless, the diagnostic value of R2* in bone marrow lesions remains controversial.…”
Section: Discussionmentioning
confidence: 99%